HUBUNGAN KEPERCAYAAN DIRI DENGAN PENYESUAIAN DIRI PADA REMAJA - Abdul Amin (Ilmu Psikologi Universitas Yudharta Pasuruan)
There are various problems experienced by teenagers, starting from development, family, relationships, health environment and their free times. One of the difficult tasks of teenagers development is adjustment, as a result of difficulty adjusting, unhappy can even be an anti-social person. and It helps teenagers to adjust to their self-confidence. The purpose of this study is to find out the relations between self-confidence and self-adjustment. The subjects in this study were students in one of the boarding schools in the Kediri, ​​East of Java and there are 50 people. The sampling technique in this study used a purposive random sampling technique. then the information uses a scale of confidence and scale of adjustment. The hypothesis proposed in this study is that there is a relations of self-confidence with adjustment. The analysis technique that used in this study is the one predictor regression analysis technique. From the regression analysis results obtained F value of reg = 4.907 with p = 0.030, so the results are significant. These results give the sense that there is an effect between self-confidence with self-adjustment. So the hypothesis which states that there is a relations between self-confidence and self-adjustment in teenagers, and is accepted.